2017
DOI: 10.3389/fpsyt.2017.00177
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Augmentation of Psychosocial and Remediation Training Efforts in Schizophrenia

Abstract: Pharmacological approaches to cognitive enhancement have received considerable attention but have not had considerable success in improving their cognitive and functional targets. Other intervention strategies, such as cognitive remediation therapy (CRT), have been shown to enhance cognitive performance but have not been found to improve functional outcomes without additional psychosocial interventions. Recently, several studies have attempted to enhance the effects of CRT by adding pharmacological interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 80 publications
2
20
0
Order By: Relevance
“…As previously reported by Lindenmayer et al ( 10 , 11 ), training neurocognitive skills may speed the path to social cognitive gains elsewhere. This may also suggest, consistent with our earlier arguments, Harvey and Sand ( 30 ) that augmentation of social cognitive training with pharmacological strategies aimed at neurocognitive abilities may be a feasible way forward as well.…”
Section: Discussionsupporting
confidence: 86%
“…As previously reported by Lindenmayer et al ( 10 , 11 ), training neurocognitive skills may speed the path to social cognitive gains elsewhere. This may also suggest, consistent with our earlier arguments, Harvey and Sand ( 30 ) that augmentation of social cognitive training with pharmacological strategies aimed at neurocognitive abilities may be a feasible way forward as well.…”
Section: Discussionsupporting
confidence: 86%
“…Among the most promising pharmacological treatments for cognitive dysfunction across bipolar disorder and unipolar disorder is erythropoietin, but the evidence is still preliminary ( 62 , 64 ). These findings are partly in accordance with findings within unipolar disorder and schizophrenia with only a few studies have shown benefit for pharmacological treatments ( 64 66 ) and with a lack of successful replication of these data ( 64 , 66 , 67 ). However, psychological treatment programs involving intensive cognitive remediation have revealed more consistent positive effects on cognition in schizophrenia ( 68 , 69 ) and emerging evidence in mood disorders ( 64 , 70 ).…”
Section: Treatment Effects On Cognitionsupporting
confidence: 87%
“…One possible path forward is to examine whether the impact of integrated cognitive remediation is boosted when combined with pharmacological therapies. This is an active area of investigation, though preliminary findings have been mixed.…”
Section: Interventions For Cognitive Impairmentsmentioning
confidence: 99%